2017
DOI: 10.1186/s13023-017-0727-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation of HOXA11 in a patient with septate uterus

Abstract: BackgroundThe etiology of Müllerian duct anomalies (MDAs) is poorly understood at present. The HOXA11 gene is crucial for the development of the Müllerian duct. The objective of this study is to report a unique case of MDAs with a novel mutation in HOXA11.ResultsWe identified a potential disease-causing mutation (p. E255K) in a patient with a septate uterus. The mutation was not detected in 169 control subjects or listed in any databases of variations. Bioinformatic predictions and functional studies showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Our patient had normal blood counts and elbow joint movements. Moreover, a heterozygous variant in HOXA11 , c.763G>A (p.Glu255Lys) has been reported as potentially cause of isolated septate uterus and spontaneous abortions but not additional anomalies in the limbs or urogenital system (Zhu et al, 2017). Another homozygous HOXA11 variant, c.775G>A (p.Glu259Lys), was recently reported as a new cause of autosomal recessive congenital anomalies of the kidney and urinary tract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our patient had normal blood counts and elbow joint movements. Moreover, a heterozygous variant in HOXA11 , c.763G>A (p.Glu255Lys) has been reported as potentially cause of isolated septate uterus and spontaneous abortions but not additional anomalies in the limbs or urogenital system (Zhu et al, 2017). Another homozygous HOXA11 variant, c.775G>A (p.Glu259Lys), was recently reported as a new cause of autosomal recessive congenital anomalies of the kidney and urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…All of the reported variants in HOXA11 are located in the homeobox domain (Figure 2e). Some reports underlined that two variants, p.Asn291ThrfsTer4, and p.Glu255Lys affected the DNA‐binding ability of HOXA11 (Horvat‐Switzer & Thompson, 2006; Zhu et al, 2017). For the variant p.Asn291ThrfsTer4 related to RUSAT, the mechanism was suggested as either haploinsufficiency or a combination of haploinsufficiency and dominant‐negative effect (Horvat‐Switzer & Thompson, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of HOXA10 was downregulated in the endometrium of MDA patients ( Zhu et al, 2016 ), and pathogenic mutations in HOXA10 have been linked to women with MDAs ( Ekici et al, 2013 ). Also, a causative mutation in HOXA11 was found in a patient with septate uterus ( Zhu et al, 2017 ). The functions of Hox genes have also been extensively investigated using mouse models.…”
Section: Technologies and Strategies To Investigate Mda Genetics And Genomicsmentioning
confidence: 99%
“…Familial septate uterus or septate uterus with other malformations have also been reported, but very rare. Previous studies have found that the mutations of HOXA10 , and HOXA11 genes are associated with the occurrence of septate uterus, but all of them are sporadic cases, lacking familial studies on the genetics of septate uterus.…”
Section: Introductionmentioning
confidence: 99%